Nanocrystalline and Amorphous Silicon Semiconductors as Competing Candidates for PV Applications (Journal of Material Science and Technology Research, 2014)
The optical properties of two Hydrogenated nanocrystalline (nc-Si: H) and amorphous silicon (a-Si: H) thin film samples are investigated using conventional spectrophotometric technique. Both samples were prepared by plasma enhanced chemical vapor deposition technique (PECVD). The nc-Si: H sample prepared with 1% silicon concentration at temperature of 220˚C with ∼1 Å/s growth rate exhibits optical behavior closer to crystalline Silicon (c-Si) sample than the a-Si: H sample prepared with Helium (He) percentage of the initial gas mixture of 20 at temperature of 80˚C with increased growth rate of ∼2.8 Å/s. The optical constants, thicknesses and the energy band gap of both samples are obtained from the transmission data only. The values of refractive index within an estimated uncertainty of 1% for both a- Si: H and nc-Si: H samples are found close to those of c-Si sample in the chosen range of wavelengths. Both samples are found to have the same optical energy gap of ~1.7 eV within an uncertainty of ~ 0.03 eV and exhibit absorption features close to those of c-Si sample. The absorption behavior in the visible and near infrared regions of electromagnetic spectrum makes both samples good candidates for photovoltaic (PV) applications.